The Effect of Point Mutations in the RYR-1 Gene on the Physicochemical Properties of Meat - N. Polozyuk, Olga; A. Svyatogorov , Nikolai; S. Polozyuk, Evgeny; E. Svyatogorova, Alexandra (KnE Life Sciences, 2021)
The impact of gene mutations in the RYR-1 gene on the physicochemical qualities and nutritional value of homozygous and heterozygous stress-resistant NOR carcasses with RSE and DFD defects was studied using molecular genetics methods. NOR, which is meat of homozygous cross-breeding pigs, had a 0.44 higher pH level, 2.62% higher water-holding ability, 2.36 units×103 higher color and 0.37% higher content of organic matter; the tryptophan content and protein-quality index were lower by 0.3 mmol/g and 0.29, respectively. This low acidity caused the denaturation of some sarcoplasmic proteins, which contributed to the loss of the meat’s water-holding ability. A sharp decrease in pH led to partial denaturation of the sarcoplasmic proteins, which determined the pale color of the PSE meat. It was found that, compared to the heterozygous stress-sensitive animals with DFD defects, the NOR pH level was 0.55 lower, the water-holding ability was 4.05% lower, and the color intensity was 4.97 units×103 lower; the protein-quality indicator amounted to 8.24, which was 1.12 higher than that in the heterozygous stress-sensitive animals with DFD defects. The defects had a significant impact on other physicochemical properties of the meat. Defects of PSE meat worsened meat color. The intensity of staining of muscle tissue with PSE defects was lower than in normal pork by 11.5, 8.7 and 6.4 units×103 , respectively. DFD-pork exceeded normal meat in color by 13.7 (P> 0.99), 9.5 (P> 0.99) and 7.4 units×103 . Keywords: stress tolerance, stress sensitivity, genotype, meat defects PSE and DFD-, RYR-1 gene, pH, water-holding ability, meat coloring